A study of relationship between school organizational climate and preschool teacher job satisfaction in Selangor - Wang, Wan Yin (2024)
This study investigates the nuanced interplay between school organizational climate and preschool teacher job satisfaction within the context of Selangor, Malaysia. Preschool education serves as a critical foundation for children's cognitive, social, and emotional development, making the satisfaction and well-being of preschool teacher’s paramount. However, the impact of the organizational climate within preschool settings on teacher job satisfaction remains underexplored, particularly within the Malaysian context. The study also investigates the relationship between school organizational climate specifically focuses on the nine subscales of organizational climate, namely supportive behaviour, directive behavior, restrictive behavior, collegial behavior, intimate behavior and disengaged behavior preschool and teachers’ total job satisfaction. This research adopted Person-Environment Occupational Performance (PEOP) model as theoretical framework and employed a quantitative correlational design. Utilizing the Hoy et al (1991) Organizational Climate Description Questionnaire (OCDQ-RE) and Spector’s (1985) Job Satisfaction Survey (JSS) as research instrument, the study was conducted using convenient sampling involving 79 preschool teachers in Selangor. These findings reveal that there is a significant positive relationship between supportive, directive, collegial, intimate, and disengaged behaviors in the organizational climate and preschool teacher job satisfaction. However, contrary to the hypothesis, the relationship between restrictive behavior and preschool teacher job satisfaction was found to be non-significant. The study's limitations include small sample size, questionnaire length affecting participation and the quantitative research method employed. It is recommended that adopted large sample size, shorten the questionnaire for better participation rates, and incorporate multiple methods of data collection.